1988
DOI: 10.1093/oxfordjournals.aje.a114983
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Craniosynostosis: Risk Indicators for the Occurrence of Craniosynostosis in Colorado

Abstract: This population-based case-control study was designed to investigate risk indicators for the occurrence of the birth defect craniosynostosis in Colorado. A total of 173 children who underwent craniectomy for craniosynostosis and 759 children without craniosynostosis were included in the study. Multivariable logistic regression analysis of birth certificate data showed that male sex (odds ratio (OR) = 1.6, 95% confidence interval (CI) = 1.1-2.2), maternal five-year age "increase" (OR = 1.3, 95% CI = 1.1-1.5), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
3
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 0 publications
9
38
3
5
Order By: Relevance
“…Most previous studies identified advanced maternal age as a risk factor for craniosynostosis [15,26,29,30] while a few [2,18], like ours, failed to show this association. This could have been due to the average young maternal age in our study and that the mothers did not make use of fertility assistance.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Most previous studies identified advanced maternal age as a risk factor for craniosynostosis [15,26,29,30] while a few [2,18], like ours, failed to show this association. This could have been due to the average young maternal age in our study and that the mothers did not make use of fertility assistance.…”
Section: Discussioncontrasting
confidence: 58%
“…It mostly occurs sporadically; the incidence of familial sagittal synostosis is in 2-6% of craniosynostosis cases, and only 8-14% of infants born with coronal synostosis are carrying an autosomal dominant disorder [2]. Several risk factors have been proposed for craniosynostosis such as white maternal race [14], smoking during pregnancy, maternal medical problems such as thyroid disease [11,12], postterm gestational age and advanced maternal age [11,15,16,17]; however, some studies do not support advanced maternal age as being an independent risk factor [16,18]. The relationship between paternal age and occurrence of craniosynostosis has not been shown [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, environmental factors such as maternal smoking, 10 nitrosatable drug use, 4,14 vitamin intake, 2 and hormonal factors such as hyperthyroidism 9 have also been shown to play roles in premature cranial suture closure, as well as advanced maternal age 11 and factors influencing fetal head constraint such as macrosomia, breech presentations, and multiple births. 1,8,11,21 Thus, demographic variabilities of craniosynostosis may be due to higher proportions of predisposed populations or higher rates of environmental exposures and maternal-fetal comorbidities. Further studies are needed to differentiate between the predisposing causes that lead to the racial and regional disproportions of craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest various risk factors for CS, such as smoking, advanced maternal age, in utero constraint, male sex, and Caucasian race-ethnicity [13][14][15][16], but its actual causes remain largely unknown. This is particularly true of non-syndromic CS, i.e., cases for which no genetic cause has been identified, which comprise about 90 % of all cases.…”
Section: Introductionmentioning
confidence: 99%